2017
DOI: 10.1039/c6ra27976g
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature pulsed CVD-grown SiO2 protective layer on TiO2 particles for photocatalytic activity suppression

Abstract: Influence of initial surface states of TiO2 on the morphology of SiO2 films grown by CVD using SiCl4 and air at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…It has been found that the growth of SiO 2 film on the TiO 2 surface is due to the hydrolysis of SiCl 4 vapor with the surface hydroxyl of TiO 2 . A similar growth mechanism was proposed for SnO 2 film since SnCl 4 can also react with hydroxyl groups .…”
Section: Results and Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…It has been found that the growth of SiO 2 film on the TiO 2 surface is due to the hydrolysis of SiCl 4 vapor with the surface hydroxyl of TiO 2 . A similar growth mechanism was proposed for SnO 2 film since SnCl 4 can also react with hydroxyl groups .…”
Section: Results and Discussionmentioning
confidence: 71%
“…However, the formation of SiO 2 film by the CVD method requires high temperatures (above 600 °C) or the presence of NH 3 as catalyst . Recently, we presented a novel room-temperature pulsed CVD method of SiO 2 on TiO 2 nanoparticles based on the reaction of SiCl 4 with surface hydroxyl groups to obtain a coating layer with an effective thickness of >3 nm to ensure the suppression of TiO 2 photocatalytic activity . However, SiO 2 coating layers with the thickness of >3 nm may also result in a significant decrease in pigment properties such as lightening power of TiO 2 because the refractive index of SiO 2 (1.46) is much lower than that of anatase TiO 2 (2.55). ,, …”
Section: Introductionmentioning
confidence: 99%
“…For instance, an ultrathin Al 2 O 3 coating was employed to improve the chemical, mechanical, and thermal stability of TiO 2 nanotube layers in extreme environments (Zazpe et al, 2017) such as for Li-ion batteries (Sopha et al, 2017a). On the other hand, a SiO 2 insulating layer was utilized to encapsulate TiO 2 nanoparticles to inhibit the photo catalytic activity, which undesirably darkens the white pigment of TiO 2 (Guo et al, 2017), and also to improve the cell compatibility and photo-killing ability (Feng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, 50% of RIF is degraded by IP-TiO 2 , which further increases to 70% for Ag@IP-TiO 2 . From the linear regression of kinetic plots shown in Figure 5f, the first-order degradation rates are determined [43]. For P25 TiO 2 , a rate of 1.52 × 10 −3 min −1 is achieved, which is above three times higher than the self-degradation rate (i.e., 0.42 × 10 −3 min −1 ).…”
Section: Photocatalytic Activity Of Ip-tio 2 and Ag@ip-tiomentioning
confidence: 99%